Pengaruh Keterampilan Pengelolaan Kelas Terhadap Efektivitas Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas XI Di SMK Negeri 1 Balige Tahun Pembelajaran 2023/2024 - Novalia Marbun; Rusmauli Simbolon; Senida Harefa; Hasudungan Simatupang; Andrianus Nababan (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The purpose of this study was to determine the existence of a positive and significant influence between classroom management skills on the effectiveness of learning Christian Religious Education and Ethics of grade XI students at SMK Negeri 1 Balige in the 2023/2024 Learning Year. The research method used is quantitative research method with inferential statistical approach. The population is all XI grade students of SMK Negeri 1 Balige in the 2023/2024 Learning Year who are Christians totaling 500 people and a research sample of 50 people was determined, namely 10% of the total population using the Random Sampling technique. Data were collected using a closed questionnaire of 35 items, of which 17 questionnaire items for variable X and 18 questionnaire items for variable Y. The results of data analysis showed a positive and significant effect of classroom management skills on the effectiveness of learning Christian Religious Education and Budi Pekerti class XI students at SMK Negeri 1 Balige for the 2023/2024 Learning Year: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.592 > rtable (a=0.05, n=50) = 0.297. b) significant relationship test obtained tcount = 5.092 > ttable (a=0.05, dk=n-2=48) = 2.021. 2) Effect test: a) Regression equation test, obtained regression equation Y ̂ = "25.24"+0.58X. b) Regression determination coefficient test (r2) = 35.1%. 3) Hypothesis testing using the F test obtained Fhitung> Ftabel = (a=0.05, dk numerator k = 18, dk denominator = n-2 = 50-2 = 48), namely 25.92> 1.51. Thus Ha, namely that there is a positive and significant effect of classroom management skills on the effectiveness of learning Christian Religious Education and Ethics of class XI students at SMK Negeri 1 Balige in the 2023/2024 Learning Year, is accepted and H0 is rejected.